Asociación entre diámetro y altura total en plantas de Cedrelinga cateniformis (Ducke) Ducke y en plantas de Osteophloeum platyspermum (A. DC.) Warb. En bosque natural. Puerto Almendra, Loreto, Perú - 2021 - Paima Ríos, Leopoldo Dante (2023)
The investigation was carried out at the CIEFOR Puerto Almendra – FCF - UNAP facilities, San Juan Bautista district, Maynas province, Loreto region. The objective was to determine the degree of association between diameter and total height in plants of Cedrelinga cateniformis (Ducke) Ducke "tornillo" and Osteophloeum platyspermum (A. DC.) Warb. “cumala blanca” in natural forest. Puerto Almendra, Loreto, Peru- 2021. The variables used were the diameter and total height of the species under study; sample 1 presented Class 1 (10cm < 20 cm) with 10 individuals; class 2 (20cm < 30cm) with 5 individuals; class 3 (30 < 40cm) with 5 individuals; class 4 (40cm < 50cm) with 5 individuals and class 5 (? 50cm) with 5 individuals; in total there were 30 individuals; for sample 2 the individuals were chosen randomly. The results indicate that there is a good to excellent relationship between diameter - total height for both species; the allometric S-Curve and logarithmic models had a better fit for the diameter-total height relationship in the species Osteophloeum platyspermum (A. DC.) Warb. “cumala blanca” and for the species Cedrelinga cateniformis (Ducke) Ducke “tornillo” were S – Curved and cubic.